Effects of the short sale circuit breaker on the stock market. (3rd July 2019) - Switzer, Lorne N.; Yue, Heng
Abstract: We provide new evidence on the effects of the recently introduced short sale circuit breaker, Rule 201, which triggers when the price of a stock drops more than 10 percent in a single day. The regulatory presumption is that the trigger should damper intraday price declines for affected stocks. However, our evidence suggests that this is not the case. The circuit breaker fails to reduce intraday volatility and intraday price declines, especially for the most volatile stocks in the market. Market quality measures based on liquidity and pricing efficiency are largely unaffected. Higher dispersion of investor opinion increases overpricing when the circuit breaker is in force. Price stabilization after stocks trigger the circuit breaker is shown for stocks that experience substantial price declines. Finally, post‐shock drift reduction is consistent with improved informational efficiency.